Future Teachers’ Training in the Context of Education Digitalization - Nataliia V.Gorbunova; Alina Khrulyova; Nataliia Konopleva (ARPHA Proceedings, 2022)
The relevance of the study is confirmed by the global problems of aging of teaching staff, insufficient popularity of the teaching profession, a high level of responsibility and requirements for teacher work (USA, Great Britain, Norway, Greece, Bulgaria) and the need to find effective ways to solve them. Modern conditions put forward new requirements for the personnel training, for the training of personnel of the future, require the search for new effective forms and methods of organizing the future teachers’ professional training, including using distance learning technologies. Higher educational institutions of Russia (V.I. Vernadsky Crimean Federal University, Kazan Federal University) accumulate, summarize and present their experience in the field of teaching staff professional training, taking into account the frontal strategy of socio-economic development of the Russian Federation, priorities 2030, regional policy. The study purpose is to conduct a pilot project for training teachers in the context of education digitalization. Research methods: theoretical methods (comparative analysis of the research subject based on the study of scientific literature and the results of modern psychological and pedagogical research); empirical methods: questioning the faculty and students of federal universities, analyzing the results of students’ activities, observing and analyzing the educational process. The study allows us to conclude that it is necessary to update the content, methodological support for the pedagogical personnel’s professional training, taking into account the requirements of the present. The practical significance of the results lies in improving the quality of teaching staff training.